Electronic, Spectral and Thermal Studies on Citronellal Thiosemicarbazone Complex of Copper(II) - Rehina, K.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Citronellal thiosemicarbzone (CTSC) forms a dimeric copper(II) complex. This complex is found to be a non-electrolyte in common organic solvents. Octahedral dimeric structure has been assigned for this novel complex based upon spectral and magnetic measurements. Electronic spectra indicated the dissociation of [CuL(Ac)(H2O)]2 into two adduct compounds under the influence of the polar solvents (pyridine, DMF, DMSO etc.). Thermal decomposition kinetics of this complex was studied by TG. The mechanism of the decomposition was found to be random nucleation. Activation energy E, pre-exponential factor A, entropy of activation ΔS and order of reaction n were calculated from the TG curves, using mechanistic and non mechanistic integral equations.